Simultaneous determination of hydroquinone and catechol using a glassy carbon electrode modified with Au@Pd loaded on reduced graphene oxide. Issue 11 (28th February 2018) - Wang, Huijuan; Zhang, Siyu; Li, Shufang; Qu, Jianying
Abstract : Au@Pd core–shell nanoplates were synthesized successfully through the heterogeneous, epitaxial growth of Au on Pd nanoplates. Abstract : Au@Pd core–shell nanoplates were synthesized successfully through the heterogeneous, epitaxial growth of Au on Pd nanoplates. The Pd nanoplates were prepared by reducing H2 PdCl4 with PVP, and then served as seeds for the nucleation of Au atoms formed by reducing HAuCl4 with citric acid. Characterization of the as-prepared Au–Pd nanoplates by scanning electron microscopy revealed that a Au shell was formed around the Pd nanoplate. In order to avoid agglomeration, the Au@Pd nanoplates were loaded onto reduced graphene to give a Au@Pd/rGO nanohybrid, which exhibited excellent electrocatalytic activity towards the redox of hydroquinone (HQ) and catechol (CC) simultaneously. The linear detection ranges were 0.01–400.00 μM for HQ and 0.10–400.00 μM for CC, with detection limits of 0.01 μM for HQ and 0.10 μM for CC. Because of the excellent performance, lower detection, wider linear range, and better selectivity, the prepared Au@Pd/rGO nanohybrid has more potential applications and has an expected application in the electrochemical sensing field.